Twierdzenie o Wzajemności Prac dla Pewnego Typu Płyt Trójwarstwowych - Gdanowicz, R. (Engineering Transactions, 1966)
This paper contains a derivation of the Betti theorem for three-layer (sandwich) plates of which the outer layers have no flexural rigidity and the middle layer carries shear forces only. An example illustrates the application of the theorem proved.